ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGADOPSIAN INTERNET BANKING - , Gusti Riza Rahman ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study presents an extended technology acceptance model that integrates innovation diffusion theory to investigate what determine to acceptance internet banking. This paper model the factors relationships such as perceived usefulness, perceived ease of use, perceived enjoyment, security and privacy, subjective norms, perceived behavioral control, and intention to adopt Internet Banking. The proposed model was empirically tested using data collected from a survey of internet banking applicant. Empirical data from regression analysis reflects that perceived usefulness and perceived enjoyment have positive influence to intention to adopt. The majority of positive relationship between perceived usefulness, subjective norms, and intention to adopt are supported by empirical data. Results also reveal that subjective norms influence perceived usefulness which affects intention to adoption internet banking. The paper concludes some important implications for the Practitioners.